Working from home during the corona-crisis is associated with higher subjective well-being for women with long (pre-corona) commutes. (February 2022) - Kroesen, Maarten
Abstract: Much research has been devoted to assessing the effect of commute duration on the subjective well-being of people, but as of yet, the respective body or research has been inconclusive as to whether there is indeed a (large) negative effect or not. To control the spread of COVID-19 governments around the world have taken unprecedented measures to control the outbreak of the Corona-virus. Forcing or strongly advising people to work from home (i.e. at least those who can) is often one of these. The ensuing situation can be considered a natural experiment; the government's intervention effectively cancels people's commuting trip and can be considered completely exogenous. Should commuting time indeed have an adverse effect on well-being, it may be expected that those workers with long (pre-corona) commutes who have transitioned to working from home will experience an increase in their well-being. This idea is tested by combining several surveys -timed before and after the crisis- from the Longitudinal Internet Studies for the Social sciences (LISS) panel, a panel that is representative of the Dutch population. In line with expectations, the results indicate that workers with a long commuting duration who transitioned to working from home indeed increased their subjective well-being. However, this effect was found to be significant only for women and not for men. A more general finding of interest is that subjective well-being did not change much between the measurements before and during the corona-crisis.